The Influence of Standard Phraseology Usage on Air Traffic Services at ACC JATSC - Fadilla Ayuningtyas; Dwi Lestary; Elfi Amir (CV. AFDIFAL MAJU BERKAH, 2026)
Effective communication between Air Traffic Controllers (ATCs) and pilots is essential to ensure safety and efficiency in air traffic management. Miscommunication, particularly in phraseology, can lead to operational errors that compromise flight safety. This study aims to analyze the influence of standard phraseology usage on the quality of air traffic services at the Area Control Center (ACC) of the Jakarta Air Traffic Service Centre (JATSC). The research employed a quantitative approach with a descriptive and correlational design. Data were collected through questionnaires distributed to 72 ATC officers selected by purposive sampling. The variables measured were compliance with standard phraseology and air traffic service quality, which includes safety, communication accuracy, and traffic flow efficiency. Data analysis was conducted using descriptive statistics and simple linear regression. The results show a significant positive correlation between the use of standard phraseology and the improvement of air traffic service quality. Consistent application of ICAO-standard phraseology enhances communication clarity, reduces ambiguity, and minimizes the risk of miscommunication. It is concluded that the use of standard phraseology is a key factor in ensuring effective and safe air traffic control operations